Trends in childhood immunisation amongst Muslim children of Punjab (India): An empirical study - Gurinder Kaur; Shaik Iftikhar Ahmed (Elsevier, 2023)
India's immunisation programme is one of the largest in the world and achieved great success over the years, however, some significant gaps are still observable in terms of achieving universal immunisation of children. Religion has emerged as a strong correlate for immunisation rates at national, state and global level. It has been observed that the rate of immunisation among children from Muslim families is comparatively less at global as well as at national level. Therefore, the paper attempts to understand immunisation trends among Muslims children from the north-western Indian state of Punjab. Based on the cross-sectional study of 400 households from district Sangrur of Punjab, results of the study show that rate of full immunisation among children from Muslim families was 88 per cent and none of the children were non-immunised. Reasons stated for partial immunisation of children included distrust of the government and belief that it would cause infertility amongst children. The present study reveals that religion per se does not appear to be influence rates of full immunisation. Geographical location, embeddedness of the community in the larger political and social milieu of their area, reach and acceptance of health workers at grassroots level emerge as strong factors contributing to higher rates of immunisation amongst Muslim children of Malerkotla.